Do the altruists lie less? - Rudolf Kerschbamer; Daniel Neururer; Alexander Gruber (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2017)
Much is known about heterogeneity in social preferences and about heterogeneity in lying aversion - but little is known about the relation between the two at the individual level. Are the altruists simply up- right persons who do not only care about the well-being of others but also about honesty? And are the selfish those who lie whenever lying maximizes their material payoff? This paper addresses those questions in experiments that first elicit subjects' social preferences and then let them make decisions in an environment where lying increases the own material payoff and has either consequences for the payoffs of others or no consequences for others. We find that altruists lie less when lying hurts another party but we do not find any evidence in support of the hypothesis that altruists are more (or less) averse to lying than others in environments where lying has no effects on the payoffs of others.
Keywords: C91; D63; D64; 330; deception; lies; social preferences; distributional preferences; equality equivalence test